2017
DOI: 10.1016/j.bone.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Timing of dental development in osteogenesis imperfecta patients with and without bisphosphonate treatment

Abstract: Bisphosphonates have established their role as medical therapy for pediatric osteogenesis imperfecta (OI) patients. Since bisphosphonates have also been shown to delay tooth development in animal models, we aimed to assess whether the medication has a similar effect on children with OI. In this cross-sectional study, bisphosphonate-treated OI patients of whom dental panoramic tomograph was taken between 3 and 16years of age formed the study group. The patients, 22 in total, had been treated with pamidronate, z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 22 publications
0
24
2
2
Order By: Relevance
“…We found that about 25% of fractures occurring in the nondeformed femurs of individuals with OI fulfill the criteria of atypical femur fractures, regardless of whether they had been exposed to bisphosphonates . Overall, systematic studies on more than 300 femur fractures have failed to detect a relationship between bisphosphonate use and diaphyseal femur fractures in OI . These studies concurred that the main risk factor for such femur fractures in OI was the severity of the underlying disease rather than bisphosphonate treatment history.…”
Section: Fracturesmentioning
confidence: 55%
See 1 more Smart Citation
“…We found that about 25% of fractures occurring in the nondeformed femurs of individuals with OI fulfill the criteria of atypical femur fractures, regardless of whether they had been exposed to bisphosphonates . Overall, systematic studies on more than 300 femur fractures have failed to detect a relationship between bisphosphonate use and diaphyseal femur fractures in OI . These studies concurred that the main risk factor for such femur fractures in OI was the severity of the underlying disease rather than bisphosphonate treatment history.…”
Section: Fracturesmentioning
confidence: 55%
“…(42) Overall, systematic studies on more than 300 femur fractures have failed to detect a relationship between bisphosphonate use and diaphyseal femur fractures in OI. (42)(43)(44) These studies concurred that the main risk factor for such femur fractures in OI was the severity of the underlying disease rather than bisphosphonate treatment history. We submit that labeling diaphyseal femur fractures that are common in OI as "atypical" because they are rare in the context of postmenopausal osteoporosis is confusing and should be avoided.…”
Section: Atypical Femur Fractures?mentioning
confidence: 70%
“…Previous concerns were that bisphosphonates may affect dental development through reduced resorption of deciduous dentition roots and surrounding bone delaying permanent dentition eruption (Bhatt et al 2014). Animal studies indicated delayed dental development (Bradaschia-Correa et al 2007), whereas recent paediatric OI data are reassuring that bisphosphonate treatment normalises rate of dental development in OI (Vuorimies et al 2017). Bisphosphonates may complicate orthodontic treatment through osteoclast inhibition decreasing tooth movement lengthening treatment time (Iglesias-Linares et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, pamidronate is used as safety medicine to reduce bone fracture in pediatric patients with osteogenesis imperfecta (OI) [ 41 ]. OI patients with pamidronate treatment show a delaying dental eruption in comparison with OI patients with naïve treatment, but not indistinguishable from normal ones [ 42 ]. Further studies will be necessary to understand the effects of pamidronate alone on cell functions including cell apoptosis and odontogenesis and the related intracellular signal transduction in SHED for pediatric patients receiving pamidronate.…”
Section: Discussionmentioning
confidence: 99%